Fate of glyphosate herbicide in munchong and benta soil series amended with cow dung and rice husk ash - Jamilu, Garba (2017)
There is increasing environmental concern on herbicide application in soils due to its toxic effect on microorganism and contamination of food chain. Glyphosate (GLY) is one of the most widely used herbicide and its commercial formulations cause toxic effect to soil microorganism, aquatic habitat and human. Investigation on fates of GLY is necessary for predicting its bioavailability and possible risk of environmental pollution. Application of organic amendments increased soil sorption ability for organic and inorganic pollutants. There is no reported study on the influences of organic amendments on fates of GLY in Malaysian soils. The present study investigates adsorption-desorption, degradation and leaching of GLY in Munchong and Benta soil series amended with cow dung (CD) or rice husk ash (RHA). The physico-chemical properties of the soils, CD and RHA were analysed at the beginning of the study. The adsorption-desorption study was conducted on the selected agricultural waste, control soils, organic matter removed (OM-removed) soils and soils incorporated with CD or RHA (10: 1 w/w) using GLY concentrations ranged between 0 and 300 mg L-1. This immediately followed by desorption study which employed addition of 0.01M CaCl2 for every decanted adsorbent from adsorption study. The degradation study was carried out using control and soils amended with 10 ton ha-1 equivalent rate of CD or RHA. All the soils were spiked with GLY, maintained at field capacity and GLY degradation was monitored for 65 days. At day’s interval, CO2 evolution was determined and on the other hand, extractable GLY residues were analyzed. Meanwhile, the enzymes dehydrogenase were assayed at the end of the incubation study. Three set of the earlier mentioned treatments each under condition of submerged, field capacity and permanent wilting point were monitored for 65 days to study soil GLY degradation at three moisture level. The column leaching study was performed by applying stimulated rainfall to GLY-spiked columns of controls and soils amended with 10 ton ha-1 equivalent rate of CD or RHA at time intervals. The leachate were collected from each interval after 24 hours of water application and analysed for GLY. At the end of the experiment, each column was divided into three layers, dried and analysed for GLY residues. All GLY residue analyses were conducted using high performance liquid chromatography. Results of the soils analysis show that, Munchong series had high clay contents and it is acidic in nature which was due to high Al saturation and contents of oxide minerals. Benta series on the other hand, was sandy in nature and had pH of near neutral. It was low in organic matter, C, N and P contents but had high CEC compared to Munchong which was due to its presence of mica and smectite. Chemical analysis of CD and RHA revealed both to be alkaline and had very low/no heavy metal contents but they have high content of Fe and Al. In addition to this, CD contains functional groups of amines, phenols, alcohols alkanes and alkenes while only siloxane, alkanes and ethers were present in RHA. The BET surface area of CD was lower than that of RHA but the former had higher internal surface area and both have relatively similar pore volume and radius. The adsorption study showed high percent (> 85%) removal of GLY by the adsorbent. The experimental isotherm data generally fitted more to Freundlich than Langmuir equation. Hence, the adsorption capacities of the adsorbents were in order of CD (Kf =1.168 mg g-1) > RHA (Kf =1.166 mg g-1). Desorption of GLY was minimal, indicating it strong adsorption to CD and RHA. Removing natural organic matter and application of CD or RHA affect the adsorption capacity of Munchong series. The sorption capacities (Kf) of the different adsorbent for GLY were in the following order: Munchong (544.879 mg g-1) > Munchong + CD (123.908 mg g-1) > Munchong + RHA (95.060 mg g-1) > OM-removed Munchong (21.538 mg g-1) > OM-removed Benta (11.572 mg g-1) > Benta + RH (1.574 mg g-1) > Benta + CD (1.405 mg g-1) > Benta (1.186 mg g-1). Adsorption of GLY by all adsorbents was favourable as indicated by Langmuir separation factor, thus, 0.011 < R ≥ 0.910. The percent desorption of GLY from Munchong series ranged between 0.013% and 2.564% with no desorption from the soils amended with CD or RHA. Meanwhile, GLY desorption from different samples of Benta series ranged between 8.10 and 14.57%. The GLY degradation occurred under natural attenuation but addition of CD and RHA stimulate microbial degradation of GLY in Munchong series while their addition showed low GLY degradation in Benta. The degradation in both soils occurred in two phase; initial rapid phase for the compound in solution and the final slow phase for the adsorbed compound. The GLY degradation data was fitted to first order exponential decay model. Munchong degradation data fitted more (0.007 < r2 ≥ 0.993) to this model than Benta (0.371 < r2 ≥ 0.757). There was higher rate of decay constant (k) for solution phase (0.0371 < k1 ≥ 0.0688) compared to sorbed phase (0.0064 < k2 ≥ 0.0475) from both soils. The half-life of GLY in Munchong from control and amended soil was less than 22 days for both solution and sorbed phase except for sorbed phase of Munchong amended with RHA which had 108.308 days. Similarly, the half-life of GLY in Benta from control and amended soil ranged from 11.476 – 41.506 days for both solution and sorbed phases. Application of GLY was shown to increase microbial respiration in Munchong while the reverse was observed in Benta hence suggesting its toxicity in the latter. The TPF concentration from control of both soils was higher compared to the treated samples indicating toxicity of GLY to soil enzyme dehydrogenase. Glyphosate was shown to rapidly degrade at field capacity in Munchong from both control and amended soils. But condition of permanent wilting points hasten GLY degradation in Benta soil applied with CD or RHA. Application of CD or RHA did not increased (p > 0.05) GLY leaching in both soils. However, more GLY residual concentration was obtained in both leachate from the soils amended with these agricultural waste, indicating their influence on increasing GLY mobility. The result of post-leaching GLY residue analysis showed its high contents at the top layer of both soils hence suggesting its low mobility in these soils even with the addition of CD or RHA. The present study therefore recommend the application of CD at the rate of 10 t ha-1 for soil GLY remediation considering its physico-chemical composition and more influence on adsorption and degradation compared to RHA. In addition to this, field capacity was recommended as appropriate soil moisture condition for enhanced GLY degradation. Field trial is also recommended to validate the present laboratory result.